Hepatic encephalopathy impacts the predictive value of the Fried Frailty Index. Issue 10 (13th August 2018) - Tapper, Elliot B.; Konerman, Monica; Murphy, Susan; Sonnenday, Christopher J.
Abstract : Frailty is increasingly recognized as a predictor of poor outcomes in solid organ transplantation. The most widely utilized frailty tool, the Fried Frailty Index (FFI), includes patient‐reported exhaustion, weight loss, and physical activity as well as measured walk speed and handgrip. Although hepatic encephalopathy (HE) is common among liver transplant candidates, data are lacking regarding its impact on the interpretation of frailty. We prospectively enrolled 685 patients with cirrhosis during their transplant evaluation, following them until death or transplantation. Our cohort was aged 54.5 ± 10.3 years, 60% male, with an average MELD score of 14.7 ± 6.3. A history of HE was present in 39%. Frailty was present in 41%, associated with higher MELD, low albumin, ascites, and HE. HE was associated with frail performance on three components of the FFI‐grip (odds ratio 1.41 95% CI, 1.03‐1.92), walk speed (1.56 95% CI, 1.14‐2.15), and decreased energy (1.44 95% CI, 1.05‐1.99). These three components were associated with transplant free survival in the whole cohort: energy (hazard ratio 1.67 95% CI, 1.25‐2.28), grip (1.63 95% CI, 1.24‐2.16), and walk speed (1.56 95% CI, 1.19‐2.04). However, among patients with HE, the FFI was not associated with survival. HE plays a critical role in the frailty phenotype and the implications of frailty among patients with cirrhosis evaluated for liver transplantation. Abstract : Hepatic encephalopathy plays an important role in the frailty phenotype and the prognostic implications of frailty among patients with cirrhosis evaluated for liver transplantation.